PENGARUH PROFITABILITAS, LEVERAGE, KOMITE AUDIT DAN KOMPLEKSITAS AUDIT TERHADAP AUDIT DELAY - Radian Atho' Al-Faruqi (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2020)
The purpose of this study was to determine the effect profitability, leverage, audit committee and audit complexity on the audit delay in mining companies listed on Indonesia Stock Exchange (BEI) in 2016-2018. Data analysis using multiple linear regression analysis. The result of the study with multiple linear regression show that simultaneously, profitability, leverage, audit committee and audit complexity affect the audit delay.Partially, leverage has a significant effect onaudit delay, while other independent variables (profitability, aucit committee and audit complexity) has not significant effect on audit delay. This research is expected to contribute knowledge an as a reference for future research based on empirical evidence regarding the effect on profitability, leverage, audit committee, and audit complexity on audit delay. For the company is expected to be able to help things that affect the audit delay.